2017
DOI: 10.1111/hiv.12572
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐exposure prophylaxis: awareness, acceptability and risk compensation behaviour among men who have sex with men and the transgender population

Abstract: With high acceptability and a low likelihood of risk compensation behaviour, PrEP can be considered as an effective prevention strategy for HIV infection among MSM and TGs in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
2
18
1
Order By: Relevance
“…However, following a brief description of oral PrEP, over half of PWID and MSM reported willingness to use PrEP, with a higher percentage of MSM than PWID expressing willingness. Our results match similar findings of low awareness but higher willingness to use PrEP among MSM and transgender individuals that have been published in India and other countries in the region, such as Myanmar, Vietnam and Thailand [16,17,[26][27][28][29][30] There is a paucity of data on awareness and willingness to use PrEP among PWID, particularly in low-or middle-income countries, which makes our study, including two key populations, unique. The wide variability in willingness to use PrEP (for both groups) across different cities was notable.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, following a brief description of oral PrEP, over half of PWID and MSM reported willingness to use PrEP, with a higher percentage of MSM than PWID expressing willingness. Our results match similar findings of low awareness but higher willingness to use PrEP among MSM and transgender individuals that have been published in India and other countries in the region, such as Myanmar, Vietnam and Thailand [16,17,[26][27][28][29][30] There is a paucity of data on awareness and willingness to use PrEP among PWID, particularly in low-or middle-income countries, which makes our study, including two key populations, unique. The wide variability in willingness to use PrEP (for both groups) across different cities was notable.…”
Section: Discussionsupporting
confidence: 90%
“…Of these, 10,538 PWID and 8,621 MSM did not self-report an HIV-positive status (i.e., they reported their HIV status as either negative or unknown) and were included in the analysis. Across the 22 study sites, the median (range) number of RDS recruitment waves was 14 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and median time to complete enrollment was 154 days (95-269). Equilibrium for the main factor of interest (i.e., PrEP awareness) was reached in all sites with the exception of one, Coimbatore (MSM), in which there were 9 waves of recruitment and awareness was still increasing (38.3% in wave 8 to 41.4% in wave 9) [7].…”
Section: General Characteristics Of Pwid and Msmmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings of participants' not feeling at sufficient risk and not knowing whether PrEP was appropriate and effective are consistent with previous studies. 21,[41][42][43][51][52][53] The discordance between these perceptions and being at risk for HIV stands out as a target in optimizing access. Perceived risk is a known determinant of health behaviours 54 and can be harnessed in promoting behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with equal access, a number of other important barriers limit PrEP use in GBM. Previous research has shown that low perceived risk for HIV [ 19 , 20 ], low social norms around PrEP (particularly among racial or ethnic minority GBM) [ 21 , 22 ], persistent PrEP stigma [ 23 ], and low uptake and adherence self-efficacy [ 24 , 25 ] are among the most important factors determining PrEP use. Unhealthy alcohol use could also make success on PrEP difficult.…”
Section: Introductionmentioning
confidence: 99%